Embodied social cognition investigated with virtual agents: The infinite loop between social brain and virtual reality: La cognition sociale incarnée étudiée avec des agents virtuels : La boucle infinie entre le cerveau social et la réalité virtuelle - Oker, A. (Frontiers in virtual reality, 2022)
While the debate regarding the embodied nature of human cognition is still a research interest in cognitive science and epistemology, recent findings in neuroscience suggest that cognitive processes involved in social interaction are based on the simulation of others’ cognitive states and ours as well. However, until recently most research in social cognition continues to study mental processes in social interaction deliberately isolated from each other following 19th century’s scientific reductionism. Lately, it has been proposed that social cognition, being emerged in interactive situations, cannot be fully understood with experimental paradigms and stimuli which put the subjects in a passive stance towards social stimuli. Moreover, social neuroscience seems to concur with the idea that a simulation process of possible outcomes of social interaction occurs before the action can take place. In this “perspective” article, we propose that in the light of past and current research in social neuroscience regarding the implications of mirror neuron system and empathy altogether, these findings can be interpreted as a framework for embodied social cognition. We also propose that if the simulation process for the mentalization network works in ubiquity with the mirror neuron system, human experimentations for facial recognition and empathy need a new kind of stimuli. After a presentation of embodied social cognition, we will discuss the future of methodological prerequisites of social cognition studies in this area. On the matter, we will argue that the affective and reactive virtual agents are at the center in conducting such research. Alors que le débat sur la nature incarnée de la cognition humaine reste un sujet d’intérêt en sciences cognitives et en épistémologie, des découvertes récentes en neurosciences suggèrent que les processus cognitifs impliqués dans l’interaction sociale reposent sur la simulation des états cognitifs d’autrui ainsi que des nôtres. Cependant, jusqu’à récemment, la plupart des recherches en cognition sociale continuaient d’étudier les processus mentaux dans l’interaction sociale en les isolant délibérément les uns des autres, suivant le réductionnisme scientifique du XIXe siècle.Récemment, il a été proposé que la cognition sociale, émergeant dans des situations interactives, ne peut être pleinement comprise à l’aide de paradigmes expérimentaux et de stimuli plaçant les sujets dans une posture passive vis-à-vis des stimuli sociaux. De plus, les neurosciences sociales semblent converger vers l’idée qu’un processus de simulation des résultats possibles de l’interaction sociale se produit avant même que l’action ne puisse avoir lieu.Dans cet article de « perspective », nous proposons qu’à la lumière des recherches passées et actuelles en neurosciences sociales, notamment en ce qui concerne les implications du système des neurones miroirs et de l’empathie, ces découvertes peuvent être interprétées comme un cadre pour la cognition sociale incarnée. Nous suggérons également que si le processus de simulation du réseau de mentalisation fonctionne en ubiquité avec le système des neurones miroirs, les expérimentations humaines sur la reconnaissance faciale et l’empathie nécessitent un nouveau type de stimuli.Après une présentation de la cognition sociale incarnée, nous discuterons de l’avenir des prérequis méthodologiques des études sur la cognition sociale dans ce domaine. À ce sujet, nous soutiendrons que les agents virtuels affectifs et réactifs occupent une place centrale dans la conduite de telles recherches.